Tumor-associated CD8+T cell tolerance induced by erythroid progenitor cells - Fan, Xue; Peng, Han; Wang, Xuesong; Sun, Yixin; Dong, Yan; Zhou, Jie; Chen, Jianfang; Huang, Shuo (Frontiers in Immunology, 2024)
CD8 + T-cell tolerance plays an important role in tumor escape. Recent studies have shown that CD45 + erythroid progenitor cells (CD45 + EPCs) generated through splenic extramedullary erythropoiesis suppress tumor immunity. However, the mechanism by which CD45 + EPCs mediate CD8 + T cell tolerance has not been fully investigated. In the present study, we found that CD45 + EPCs take up soluble proteins, present antigenic epitopes on their surface, and induce antigen-specific CD8 + T cell anergy. In addition, we found that CD45 + EPC directly nitrates tyrosine within the TCR/CD8 complex via the production of reactive oxygen species and peroxynitrite, preventing CD8 + T cells from responding to their specific peptide antigens. Furthermore, uric acid treatment effectively abolished the immunosuppressive effects of CD45 + EPCs during CD8 + T cell adoptive transfer, thereby enhancing the anti-tumor efficacy. These results demonstrated that CD8 + T cell tolerance in tumorbearing mice is induced by CD45 + EPCs. The results of this study have direct implications for tumor immunotherapy.